Prevalance of Inducible Beta-Lactamases in Hospital Acquired Pseudomonas Aeruginosa - Çelik, İlhami; Cihangiroğlu, Mustafa; Akbulut, Ayhan (Fırat University, 2007)
Objectives: Existence of inducible beta-lactamases (IBL) at hospital acquired Gram negative bacteria causes to problem to treat infections on clinical basis. Resistance may occur to many beta-lactam antibiotics including new ones during treatment and thus, treatment can remain insufficient. Materials and Methods: In this study, existence of IBL studied with the direct induction method at 50 Pseudomonas aeruginosa strains that isolated different clinical specimens of the patients who diagnosed as hospital acquired infections. Results: IBL existence was detected the most at P. aeruginosa strains isolated from wound specimens. Three strain to ceftazidim, 16 to ceftriaxone and 24 to cefotaxime were seen as susceptible on routin antibiotic disk sucsebtibility test among the 41 strains detected produce IBL. Conclusion: To eliminate this artificial sensitivity, disks must be arranged to detect the IBL on antibiotic susceptibility test. ©2007, Fırat University, Medical Faculty

Giriş: Hastane kaynaklı Gram-negatif bakterilerdeki indüklenebilir beta-laktamaz (İBL) varlığı, klinik açıdan ciddi problemlere neden olmaktadır. Yeni beta-laktamlar başta olmak üzere tedavi sırasında bir çok beta-laktam antibiyotiğe direnç gelişebilmekte ve tedavi yetersiz kalmaktadır. Gereç ve Yöntem: Çalışmamızda hastane infeksiyonu tanısı almış hastalardan alınan çeşitli örneklerden izole edilen 50 Pseudomonas aeruginosa suşunda direkt indüksiyon yöntemiyle İBL varlığı araştırıldı. Bulgular: En sık yaradan izole P.aeruginosa suşlarının İBL salgıladığı belirlendi. İBL saptadığımız 41 suşa yapılan rutin antibiyogramda üçü seftazidime, 16'sı seftriaksona ve 24'ü sefotaksime duyarlı görünmekteydi. Sonuç: Bu yalancı duyarlılık sorununun giderilmesi için antibiyogramda disk diziliminin İBL üretimini saptayacak şekilde yapılması gerekmektedir. ©2007, Fırat Üniversitesi, Tıp Fakültesi
Hastane Kökenli Pseudomonas Aeruginosa Suşlarında İndüklenebilir Beta-Laktamaz Sıklığı